2021
DOI: 10.1111/jocn.16185
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Morse Fall Scale and the Johns Hopkins Fall Risk Assessment Tool for fall risk assessment in an acute care setting

Abstract: Aims and Objectives:To evaluate the measured fall risk score that more accurately reflects the changeable conditions in acute care settings, and to efficiently evaluate the association between falls and fall risk score. Background:The Morse Fall Scale (MFS) is a well-known easy-to-use tool, while the Johns Hopkins Fall Risk Assessment Tool (JHFRAT) consists of items with high specificity. Evaluating suitable fall-risk assessment tools to measure these changeable conditions may contribute to preventing falls in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
(69 reference statements)
0
9
1
Order By: Relevance
“…The patients' fall risk was evaluated using the JHFRAT 8 . This is a widely used, valid, and reliable tool for fall risk stratification during hospitalization for the adult population 16,17 . The JHFRAT includes seven items considered to influence the risk of falls including age, fall history, urinary frequency and/or incontinence, medications (e.g., PCA/opiates, anticonvulsants, anti‐hypertensives, diuretics, hypnotics, laxatives, sedatives, and psychotropics), equipment that tethers patient (e.g., lines, tubes), mobility, and cognition.…”
Section: Methodsmentioning
confidence: 99%
“…The patients' fall risk was evaluated using the JHFRAT 8 . This is a widely used, valid, and reliable tool for fall risk stratification during hospitalization for the adult population 16,17 . The JHFRAT includes seven items considered to influence the risk of falls including age, fall history, urinary frequency and/or incontinence, medications (e.g., PCA/opiates, anticonvulsants, anti‐hypertensives, diuretics, hypnotics, laxatives, sedatives, and psychotropics), equipment that tethers patient (e.g., lines, tubes), mobility, and cognition.…”
Section: Methodsmentioning
confidence: 99%
“…If a patient had fallen, the last fall risk level before a fall was extracted for the predictive validity analysis. If the patient had not fallen, the highest fall risk level was extracted (Kim et al, 2022). Predictive validity of the two fall assessment methods were sensitivity (high‐risk patients among fallers), specificity (non‐high‐risk patients among non‐fallers), positive predictive value (PPV, among high‐risk patients who fall), and negative predictive value (NPV, among non‐high‐risk patients who never fall) (Poe et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The caliper value was taken as 0.02, and the 1:1 adjacent matching method was used to screen patients from the control group. To analyze the predictive validity of the two methods, the sensitivity, specificity, PPV, and NPV were calculated using the data before PSM (Kim et al, 2022). Also, the area under the receiver operating characteristic curve (AUC) was analyzed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of nine tools were used to assess patients' fall risk in medical institutions. Commonly used tools included the Morse Fall Scale (MFS), Johns Hopkins Hospital Fall Risk Assessment Tool (JHFRAT), Hendrich II Fall Risk Model (HFRM II), Bobath Memorial Hospital Fall Risk Assessment Scale (BMFRA), and St. Thomas's Risk Assessment Tool in Falling Elderly Inpatients (STRATIFY) [30][31][32][33][34][35][36][37][38]. The sensitivity, specificity, positive predictive value, negative predictive value, area under the receiver operating characteristics curve, and Youden index, determined with study-specific cutoff scores, are shown in Table 2.…”
Section: Fall Risk Assessmentmentioning
confidence: 99%